The “locus amoenus”: “ergon” or “parergon” in loneliness - Márquez, Miguel Ángel (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
This paper shows how the locus amoenus, which is originally a frame for bucolic drama (a parergon in Guillén's terminology), is converted into an empty scene for an impossible drama in Agathias” bucolic epigram, and into an ergon full of nostalgia and melancholy in Luis Cernuda's “Egloga”.
Keywords: Locus amoenus; bucolic poetry